Inhibition of PI3K/AKT molecular pathway mediated by membrane estrogen receptor GPER accounts for cryptotanshinone induced antiproliferative effect on breast cancer SKBR-3 cells - Danning Shi; Piwen Zhao; Lixia Cui; Hongbo Li; Liping Sun; Jianzhao Niu; Meng Chen (BMC, 2020)
Abstract Background Breast cancer is the most frequently diagnosed malignancy among women and the second leading cause of cancer death worldwide. Among which nuclear estrogen receptor (nER) negative breast cancer is always with much poor prognosis. Recently, membrane G protein coupled estrogen receptor (GPER), a newly recognized estrogen receptor has been documented to take essential part in the development and treatment of breast cancer. The present study was designed to investigate the anti nER negative breast cancer effect of cryptotanshinone (CPT), an important active compound of traditional Chinese medicine Danshen and its possible molecular pathway. Methods The following in vitro tests were performed in nER negative but GPER positive breast cancer SKBR-3 cells. The effect of CPT on cell proliferation rate and cell cycle distribution was evaluated by MTT cell viability test and flow cytometry assay respectively. The role of PI3K/AKT pathway and the mediated function of GPER were tested by western blot and immunofluorescence. Technique of gene silence and the specific GPER agonist G-1 and antagonist G-15 were employed in the experiments to further verify the function of GPER in mediating the anticancer role of CPT. Results The results showed that proliferation of SKBR-3 cells could be blocked by CPT in a time and dose dependent manner. CPT could also exert antiproliferative activities by arresting cell cycle progression in G1 phase and down regulating the expression level of cyclin A, cyclin B, cyclin D and cyclin-dependent kinase 2 (CDK2). The antiproliferative effect of CPT was further enhanced by G-1 and attenuated by G-15. Results of western blot and immunofluorescence showed that expression of PI3K and p-AKT could be downregulated by CPT and such effects were mediated by GPER which were further demonstrated by gene silence test. Conclusion The current study showed that the antiproliferative action of CPT on SKBR-3 cells was realized by inhibition of GPER mediated PI3K/AKT pathway. These findings provide further validation of GPER serving as useful therapeutic target.